STUDENT EVALUATION OF USING SELF-REFLECTION LOGS: THE VALUE OF USING SELF-REFLECTION MATERIALS IN AN EFL UNIVERSITY COURSE IN JAPAN - Maher, Kate (PEOPLE: International Journal of Social Sciences, 2015)
This study reports on the utilization of a student self-reflection log within a first-year university EFL course to examine the perceived value of self-reflection by the students for their English studies. Through using the log, students reflected on what they did inside of class, what they felt was successful, and what they would like to improve. The objective of the study was to examine what value the students felt the self-reflection logs had for their English studies. A post-course evaluation questionnaire and delayed post-course interviews were carried out to answer the following research questions: Would students regard the self-reflection logs as a valuable tool for learning English? What elements of using the logs would be valuable for the students? The results showed that the participants’ evaluation of using a self-reflection log was positive, and that their motivation and learning behavior had improved through weekly self-reflection and goal setting. It can be claimed that the self-reflection logs were perceived as being of value to the participants for their English learning